2019
DOI: 10.3389/fpsyt.2018.00762
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise in Major Depression: Reducing the Mortality Gap While Improving Clinical Outcomes

Abstract: Major depression shortens life while the effectiveness of frontline treatments remains modest. Exercise has been shown to be effective both in reducing mortality and in treating symptoms of major depression, but it is still underutilized in clinical practice, possibly due to prevalent misperceptions. For instance, a common misperception is that exercise is beneficial for depression mostly because of its positive effects on the body (“from the neck down”), whereas its effectiveness in treating core features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 170 publications
1
74
0
5
Order By: Relevance
“…Suicide is the third most common cause of death in adolescents (2). In general, depression is associated with a shorter lifespan (32).…”
Section: Characteristics Of Depression In Children and Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicide is the third most common cause of death in adolescents (2). In general, depression is associated with a shorter lifespan (32).…”
Section: Characteristics Of Depression In Children and Adolescentsmentioning
confidence: 99%
“…Physical activity interventions have shown to be efficient not only to produce therapeutic benefits when implemented solely or as a part of a treatment for mental disorders, but also to prevent or delay the appearance of mental disorders (49). Additionally, physical exercise was found to be effective in treating symptoms and in reducing the mortality related to major depression (32). As this review discusses, meta-analyses on the depression-reducing effect of exercise in children and adolescents (50-53) so far suggest small to medium effects in this age group.…”
Section: Physical Exercise and Its Beneficial Impact On Healthmentioning
confidence: 99%
“…Several studies have demonstrated that aerobic exercise (AE) could represent a non-pharmacological strategy to improve the treatment of depression, decreasing, at the same time, the burden of somatic comorbidity of this pathology (Mura and Carta, 2013;Josefsson et al, 2014). Since the 1980s, several papers have reported on the beneficial effects played by exercise and physical activity in the treatment of depression, effects comparable to those of antidepressants (Martinsen et al, 1985;Babyak et al, 2000;Belvederi Murri et al, 2018;Lopez-Torres Hidalgo, 2019). This increased interest in this field has led to the proposal that physical exercise may serve as an alternative or integrative approach in combination with monoaminergic drugs for the treatment of MDD (Martinsen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…9,12 More importantly, exercise can improve cardiorespiratory fitness, an independent predictor of all-cause mortality. 18 In Brazil, exercise prescription and supervision are roles usually associated with exercise professionals. 19 However, encouraging a healthier lifestyle is the duty of all mental health professionals (MHP) involved in patient care.…”
Section: Introductionmentioning
confidence: 99%